Education on Women's Workers' Rights and Reproductive Health in Industrial Environments - Rifki Suwaji; Rina Indra Sabella; Fida Oktafiani; Waloyo Waloyo; Siti Masruroh (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
This community service program aims to improve women workers' understanding of labor rights and reproductive health in the industrial environment of Sidoarjo Regency, East Java. The method used was participatory action research (PAR) involving 80 core participants representing women's organizations, labor unions, and CSR units of local industrial companies. The activities were carried out through interactive lectures, group discussions, case simulations, and role-plays designed to address the limitations of legal and health literacy among women workers. The results of the activity showed a significant increase in participants' knowledge, from an average pre-test score of 56.4 to 87.6 in the post-test, an increase of 31.2 points. In addition, this activity also identified key issues, namely low understanding of labor rights, the lack of reproductive health facilities in the workplace, and the socio-cultural stigma that makes reproductive issues considered taboo. To ensure the program's sustainability, the Sidoarjo Women's Workers Forum was established as a cross-organizational advocacy platform focused on promoting workers' rights, advocating for the provision of lactation rooms, and strengthening gender advocacy units within labor unions. Overall, this activity successfully achieved more than 90% of its target outputs and made a significant contribution to the achievement of the Sustainable Development Goals (SDGs), particularly in the areas of gender equality and decent work. The implication of this activity is the need for similar programs to be replicated in other industrial areas with multi-stakeholder support to strengthen the protection of women workers' rights in Indonesia.